Pengaruh Pelatihan Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Command Center 112 Kota Surabaya - Aulia, Dwi Indah Nurul (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This study aims to analyze the effect of job training and physical work environment on employee performance at Command Center 112 Surabaya City. Command Center 112 is an emergency response service that requires optimal performance from every employee to provide maximum public services. This study uses a quantitative approach with multiple linear regression methods. Data was collected through questionnaires distributed to 80 respondents who are all employees of Command Center 112 Surabaya City using saturated sampling technique. Data analysis was performed using SPSS version 25. The results showed that job training has a positive and significant effect on employee performance with a t value of 2.884 and a significance level of 0.005. Conversely, the physical work environment has no significant effect on employee performance with a t value of 0.601 and a significance level of 0.550. The R Square value of 0.113 indicates that both independent variables can explain 11.3% of the variation in employee performance. These findings indicate that improving the quality of job training is a key factor in improving the performance of Command Center 112 employees, while the already good physical work environment conditions do not require significant improvements to enhance performance.